MEGF8 is a modifier of BMP signaling in trigeminal sensory neurons - Caitlin Engelhard; Sarah Sarsfield; Janna Merte; Qiang Wang; Peng Li; Hideyuki Beppu; Alex L Kolodkin; Henry M Sucov; David D Ginty (eLife, 2013)
Bone morphogenetic protein (BMP) signaling has emerged as an important regulator of sensory neuron development. Using a three-generation forward genetic screen in mice we have identified Megf8 as a novel modifier of BMP4 signaling in trigeminal ganglion (TG) neurons. Loss of Megf8 disrupts axon guidance in the peripheral nervous system and leads to defects in development of the limb, heart, and left-right patterning, defects that resemble those observed in Bmp4 loss-of-function mice. Bmp4 is expressed in a pattern that defines the permissive field for the peripheral projections of TG axons and mice lacking BMP signaling in sensory neurons exhibit TG axon defects that resemble those observed in Megf8−/− embryos. Furthermore, TG axon growth is robustly inhibited by BMP4 and this inhibition is dependent on Megf8. Thus, our data suggest that Megf8 is involved in mediating BMP4 signaling and guidance of developing TG axons.